The herbicide cycloxydim is an effective alternative to propyzamide or glyphosate for the control of the forest grass weeds Molinia caerulea, Calamagrostis epigejos, Deschampsia flexuosa and Holcus lanatus. (7th August 2021) - Willoughby, Ian H; Forster, Jack
Abstract: We tested the efficacy of a range of herbicides to see if they might be potential substitutes for the use of propyzamide or glyphosate to control grass weed species that, if left unchecked, often outcompete recently planted trees in UK forests. Applications of 0.45kg a.i. ha −1 cycloxydim in late April–early May gave good control of wood small reed ( Calamagrostis epigejos (L.) Roth), Yorkshire fog ( Holcus lanatus L.), and wavy hair grass ( Deschampsia flexuosa (L.) Trin.)) for at least 12 weeks after application. When coupled with a sequential application of 0.15kg a.i. ha −1 propaquizafop made 5 weeks later, purple moor grass ( Molinia caerulea (L.) Moench) was controlled for at least 21 weeks. Sequential applications of 0.45 kg a.i. ha −1 cycloxydim in October, then 0.45 kg a.i. ha −1 cycloxydim in late April, was the most effective treatment for minimizing competition from purple moor grass, wood small reed or wavy hair grass and equally effective as propyzamide on Yorkshire fog. The herbicides carbetamide, clethodim, clodinafop-propargyl and fenoxaprop-p-ethyl were not as effective as cycloxydim. We conclude that cycloxydim is effective on a broader range of grass weeds than previously thought. Cycloxydim and propaquizafop are both highly selective and unlike the broad-spectrum herbicide glyphosate will not harm young trees, even if they are oversprayed when in active growth. If applied at the correct time of year, cycloxydim is likely to be as effective as glyphosate on most grasses, and for wood small reed, purple moor grass and wavy hair grass considerably more effective than propyzamide. A sequential application of cycloxydim or possibly propaquizafop in the autumn, followed by a second spray in late April of the following spring, is likely to be the most effective means of maximizing tree growth and survival in grass dominated new planting or restock sites in UK forests.